A new approach to endometrial cancer subtyping – a hope for a milestone in correct patient triaging - Adamczyk-Gruszka, Olga (Medical Studies/Studia Medyczne, 2023)
Endometrial cancer is the most common cancer of the female genital organs. For many years the prognosis was based on histopathological grade and type. The pathological identification of endometrial carcinomas included two types. Type I – endometrioid (EEC), similar to the endometrium – was characterized by genetic predisposition, obesity, polycystic ovary syndrome, anovulatory cycles, and irregular menstruation resulting from hyperestrogenism, which is the main predisposing factor for the development of type I EC. Type II included serous, clear cell, and undifferentiated carcinomas. Here were observed older patient’s age, higher clinical stage to compare with non-endometrioid histology, and finally poorer prognosis. The Cancer Genome Atlas (TCGA) study found mutations in several endometrioid and serous cancer genes. The TCGA has identified four molecular subclasses based on somatic mutation burden and copy number variations. Recent data show the prognostic value of TCGA subclasses because they correlate with patient survival.